A Survey Of Perceived Barriers And Motivators Towards Exercise Among People With Parkinson’s Disease In Malaysia - Krishnan Vasanthi, Rajkumar; Choo Kher Ying, Alfonsa (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Considerable amount of evidence supports that exercise plays a vital role in maintaining and slowing Parkinson's disease (PD) progression. However, some people with PD have remained sedentary for undefined reasons. Therefore, the perceived barriers and motivators towards exercise among people with PD among Malaysian were investigated. METHODS: A cross-sectional survey was conducted using a self-developed and validated questionnaire distributed to forty-seven people with PD in a non[1]governmental organisation to determine exercise barriers and motivators. RESULTS: The exercise motivators in the study were having an exercise instructor (83.0%), exercise makes them feel healthier and more energetic (83.0%), and constant encouragement from family and friends (80.9%). The exercise barriers reported in this study were fatigue (40.4%) fear of falling (34%), bad weather (38.2%), and lack of transportation (31.9%). CONCLUSION: The study concluded that people with PD exercised because it makes them feel healthier and more energetic. Besides that, having an exercise instructor and being encouraged by family and friends reported being exercise motivators among the people in this study. The exercise barriers reported in this study were fatigue, bad weather, fear of falling, and lack of transportation. These findings should be taken into consideration when developing strategies and health interventions to improve exercise participation for people with PD.